Current status of the Saker Falcon in Russia and Kazakhstan - Igor V. Karyakin; Elvira G. Nikolenko; Elena P. Shnayder (Пернатые хищники и их охрана)
The range and abundance of Saker Falcon (Falco cherrug) in Russia and Kazakhstan are systematically declining. It is no exaggeration to say that the Saker Falcon is by far the most endangered raptor species in the Palaearctic. A compilation of literature data shows the species’ estimated abundance in 1970s Russia was at least 9,000–10,000 pairs (Galushin, 2004; Karyakin, 2008), while it appears over 15,000 pairs nested in Kazakhstan – in the 1990s their abundance there was estimated at 5,218 (4,808–5,628) pairs.